Evaluation of the Relationship between Death Perspectives of Doctors Working in the Emergency Department and Termination of Resuscitation - Salih Denis Simsek; Ali Karakus; Mustafa Polat; Okkes Zortuk; Anil Iflazoglu; Pınar Yücel Bayar (CHRISMED Journal of Health and Research)
Introduction: Criteria for terminating resuscitations have been identified in the literature such as no VF/VT rhythm during cardiopulmonary resuscitation (CPR). People’s perception of death varies depending on social, geographical, cultural, and educational factors. The Death Perception Scale (DPS) was developed to measure these variations. This study aims to evaluate the relationship between individuals’ perspectives on death, the CPR process they apply in the emergency room, and the factors that affect it. Materials and Methods: The study was conducted on physicians working in emergency departments in Hatay province. The participating physicians completed a 39-question test, which included multiple-choice and DPS questions, to record their demographic data, education, and the situations they consider when terminating CPR. The data were collected digitally. IBM SPSS 27 and GraphPad Prism were used for data analysis. Results: 79 physicians participated in the study, the mean age of these physicians was 27.53 ± 3.61, and 45.6% were female. The average tenure as a physician was 2.81 years, while the average duration of work in the emergency department was 2.25 years. No statistically significant relationship was found between the change in the duration of working in the emergency department and the change in the medical profession and DPS among the physicians included in the study. No relationship was found between the degree of the physician (general practitioner, resident, and specialist) and the CPR termination times of the patients. Conclusions: Analyzing individual characteristics with objective values while managing a terminally ill patient will enhance perceptual integrity.